The impact of intellectual disability nurse specialists in the United Kingdom and Eire Ireland: An integrative review - Jennifer Bur; Karen Missen; Simon Cooper (Wiley, 2021)
Abstract Aim To identify and evaluate the impact of Intellectual Disability Nurse Specialists person‐centred care for people with intellectual disability. Design An Integrative review of the literature was performed between January 2007-December 2017. Methods Searching the PubMed Library of Medicine, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Medline Ovid, PsychINFO, Health Source: Nursing/Academic edition. A total of eight articles were selected for the final study example, including four mixed methods studies and four qualitative studies. Results Three Intellectual Disability Nurse Specialist models were evaluated, and three main themes emerged: person‐centred care, organizational and practice development. Conclusion The Intellectual Disability Nurse Specialist expert knowledge and skills contribute to the development of effective systems and processes. The results highlighted the complex nature of the Intellectual Disability Nurse Specialist role and the importance of ongoing development, promotion and evaluation and their contribution to care in the healthcare setting.